2020
DOI: 10.2147/ndt.s264300
|View full text |Cite
|
Sign up to set email alerts
|

<p>Metabolic Syndrome Predicts Poor Outcome in Acute Ischemic Stroke Patients After Endovascular Thrombectomy</p>

Abstract: Background and Aims The metabolic syndrome (MetS) is believed to contribute to a higher probability of developing cardiovascular diseases. This study aimed to investigate whether MetS could predict the prognosis in ischemic stroke patients after endovascular thrombectomy (EVT). Methods Between January 2016 and September 2019, patients treated with EVT due to large vessel occlusions in anterior circulation were prospectively recruited. MetS was defined using the Internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…72 However, these results are not always reproducible as seen in Bouslama et al 73 (n=926), which could not find an association between BMI and outcomes after mechanical thrombectomy due to large vessel occlusive acute ischemic stroke. Also, Chen et al 74 (n=248) reported that metabolic syndrome (which measures obesity according to waist circumference) was associated with increased risk of unfavorable functional outcome at 90 days in ischemic stroke treated with endovascular treatment, but was not associated with mortality. However, this study had a small sample size and metabolic derangement ascribed to metabolic syndrome had a stronger influence on outcomes more than pure obesity.…”
Section: Neurointerventional Implicationsmentioning
confidence: 99%
“…72 However, these results are not always reproducible as seen in Bouslama et al 73 (n=926), which could not find an association between BMI and outcomes after mechanical thrombectomy due to large vessel occlusive acute ischemic stroke. Also, Chen et al 74 (n=248) reported that metabolic syndrome (which measures obesity according to waist circumference) was associated with increased risk of unfavorable functional outcome at 90 days in ischemic stroke treated with endovascular treatment, but was not associated with mortality. However, this study had a small sample size and metabolic derangement ascribed to metabolic syndrome had a stronger influence on outcomes more than pure obesity.…”
Section: Neurointerventional Implicationsmentioning
confidence: 99%
“…higher pre-thrombectomy blood/serum glucose was significantly associated with an unfavourable functional outcome: WMD = 1.34 mmol/L (95%CI 0.97 to 1.72; Z = 12.3) p < 0.00001 (Figure 2). Most [N = 13/19 (68%)] individual studies reported significantly higher glucose in unfavourable outcome groups (Shi et al, 2014;Jiang et al, 2015;Ozdemir et al, 2015;Zi et al, 2017;Kim et al, 2018;Huo et al, 2019;Sallustio et al, 2019;Wu et al, 2019;Broocks et al, 2020;Chen et al, 2020;Suissa et al, 2020;Nisar et al, 2021;Sun et al, 2021) (Supplementary Table S6), including the highest weighted study [ (Zi et al, 2017); N = 698], although the WMD was not large. This was the case for most high weighted studies, apart from Chen et al (2020).…”
Section: Continuous (Ratio) Glucose (Mmol/l)mentioning
confidence: 99%
“…Most [N = 13/19 (68%)] individual studies reported significantly higher glucose in unfavourable outcome groups (Shi et al, 2014;Jiang et al, 2015;Ozdemir et al, 2015;Zi et al, 2017;Kim et al, 2018;Huo et al, 2019;Sallustio et al, 2019;Wu et al, 2019;Broocks et al, 2020;Chen et al, 2020;Suissa et al, 2020;Nisar et al, 2021;Sun et al, 2021) (Supplementary Table S6), including the highest weighted study [ (Zi et al, 2017); N = 698], although the WMD was not large. This was the case for most high weighted studies, apart from Chen et al (2020). Shriki et al (2020) and Karamchandani et al (2022) displayed non-significant differences in the opposite direction but were small, low weighted studies.…”
Section: Continuous (Ratio) Glucose (Mmol/l)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that stroke with MetS shows poor prognosis. In addition, stroke survivors with MetS also show the higher mortality rate and stroke recurrence than those without MetS [6]. Since stroke produces a great socioeconomic burden and the current therapeutic strategy is still limited, it is very essential to prevent it [7].…”
Section: Introductionmentioning
confidence: 99%